Letter from Carl D. Duncan to Patricia Whiting, March 18, 1965 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan attempts to coordinate planning and scheduling with Whiting. He briefly mentions an outing at a ranch and includes a poem titled "It Must be Your Propensity."